Food security, agriculture, and poverty in Asia - Warr, Peter (International Food Policy Research Institute, 2013)
A central policy question for Asia and other food-insecure regions of the world is how to respond to the threat posed by food inse-curity. In particular, is it more effective to promote improvements in agricultural productivity or to pursue price interventions aimed at promoting food self-sufficiency at a national level? In this paper I want to present some recent evidence on undernourishment and some other dimensions of food security in Asia and elsewhere that are relevant for this question. The key underlying research questions are: what drives changes in food security; and what does this imply for agricultural and food policy?